Zambia Then and Now : Colonial Rulers and Their African Successors. - Grant, William (Kegan Paul Africa Library., 2009)
Written by a member of the last generation of British Colonial Service Officers in Africa, the book seeks to place both colonial rulers and their African successors in the context of history and the circumstances of their time, viewing their achievements and failures critically but not unsympathetically and comparing colonial society with that of the independent African country that Northern Rhodesia has become.